SP0196 IS THERE ROOM FOR OTHER IMAGING MODALITIES BEYOND CONVENTIONAL X-RAYS AND MRI?. (June 2019) - van der Laken, C.J.
Abstract : Early diagnosis of spondyloarthritis is still tempting since objective measures to assess disease activity are often negative. MRI provides highly sensitive visualization of inflammation, but detection levels in early spondyloarthitis are varying. Another clinical temptation is early treatment evaluation of spondyloarthritis. An important outcome measure is therapeutic efficacy on bone formation in vertebral column and sacro-iliac joints. Conventional X-rays only allow for assessment of bone formation over a time span of at least 2 years. In this presentation, opportunities with new upcoming imaging techniques to address above mentioned clinical issues will be discussed in relation to longer existing imaging techniques. Disclosure of Interests: None declared